Design and Implementation of a Web-Based Document Archive Application at the North Sumatra Education Quality Assurance Agency - Naina Nazwa Hasibuan; Tiara Bela Harahap; Mhd. Furqan (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
Document archiving management is an important aspect of administrative activities in institutions. Manual archiving processes often cause problems such as delays in document retrieval, risk of data loss, and inefficiency in report preparation. This study aims to design and develop a web-based document archiving application that can manage incoming and outgoing documents in a structured and integrated manner. The research method consists of data collection, system requirements analysis, system design, application implementation, and functional testing. The application is developed using PHP as the server-side programming language, MySQL as the database management system for data storage, and the Bootstrap framework to create a responsive and user-friendly interface. The results show that the developed application is able to store, manage, and display document data properly, as well as provide document recap features based on specific periods. Therefore, this web-based document archiving application can improve the effectiveness, efficiency, and security of document management.